If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2 + -4) = x + -3 Combine like terms: 2 + -4 = -2 5(-2) = x + -3 Multiply 5 * -2 -10 = x + -3 Reorder the terms: -10 = -3 + x Solving -10 = -3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + -1x = -3 + x + -1x Combine like terms: x + -1x = 0 -10 + -1x = -3 + 0 -10 + -1x = -3 Add '10' to each side of the equation. -10 + 10 + -1x = -3 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = -3 + 10 -1x = -3 + 10 Combine like terms: -3 + 10 = 7 -1x = 7 Divide each side by '-1'. x = -7 Simplifying x = -7
| 5000(.039)=(.065)x | | (3x-2y+5)+(4x+6y-1)= | | 2f-4=2 | | v^2+7.3v-65.7=0 | | 6x+8=-72-6x | | x=1000*0.325*18 | | x+10x+35x+50x+24= | | f(1.382)=x^5+6x^4-2x^3-x^2-2x+9 | | 3f+6=15 | | (18+2X)(12+2X)=324 | | a+5=-5a+55 | | 1=.45+.54-x-441 | | 6[6-(-9X-7)]=270X+246 | | v^2+6.6v-51.48=0 | | 64x-4=28x | | 9(-2x+2x+5)=-5-2(3-x)+4(6-x) | | 3x^2-5x-88=0 | | -20=-7x+3(x-5) | | 2(x+7)+2x=30 | | 2w=7w | | -x^3+x^2+36*x-23=0 | | -20=-7+3(x-5) | | 2x-3=12x+43 | | A+5+b+7a+(-2)-b= | | v^2+7v-56=0 | | (c+1)+3C+48=180 | | w-23.5=42.5 | | 5x+38=12x | | 9+10=21*1 | | 4=-2x-25 | | 6+0.5x=42 | | 3a+8=26 |